Dimethyl Fumarate Strongly Ameliorates Gray and White Matter Brain Injury and Modulates Glial Activation after Severe Hypoxia–Ischemia in Neonatal Rats - Jon Ander Alart; Antonia Álvarez; Ana Catalan; Borja Herrero de la Parte; Daniel Alonso-Alconada (Antioxidants)
Neonatal hypoxia–ischemia is a major cause of infant death and disability. The only clinically accepted treatment is therapeutic hypothermia; however, cooling is less effective in the most severely encephalopathic infants. Here, we wanted to test the neuroprotective effect of the antioxidant dimethyl fumarate after severe hypoxia–ischemia in neonatal rats. We used a modified Rice–Vannucci model to generate severe hypoxic–ischemic brain damage in day 7 postnatal rats, which were randomized into four experimental groups: Sham, Sham + DMF, non-treated HI, and HI + DMF. We analyzed brain tissue loss, global and regional (cortex and hippocampus) neuropathological scores, white matter injury, and microglial and astroglial reactivity. Compared to non-treated HI animals, HI + DMF pups showed a reduced brain area loss (p = 0.0031), an improved neuropathological score (p = 0.0016), reduced white matter injuries by preserving myelin tracts (p < 0.001), and diminished astroglial (p < 0.001) and microglial (p < 0.01) activation. After severe hypoxia–ischemia in neonatal rats, DMF induced a strong neuroprotective response, reducing cerebral infarction, gray and white matter damage, and astroglial and microglial activation. Although further molecular studies are needed and its translation to human babies would need to evaluate the molecule in piglets or lambs, DMF may be a potential treatment against neonatal encephalopathy.